Chapter 4: Partial Differentiation
Section 4.3: Chain Rule
If u=Fy−xx y,z−xx z, show that x2 ux+y2 uy+z2 uz=0.
It is most convenient to define rx,y,z=y−xx y and sx,y,z=z−xx z so that x2 ux+y2 uy+z2 uz becomes x2 Fr rx+Fs sx+y2 Fr ry+Fs sy+z2 Fr rz+Fs sz. The following calculation then results from an application of the chain rule.
x2 ux+y2 uy+z2 uz
=x2 Fr rx+Fs sx+y2 Fr ry+Fs sy+z2 Fr rz+Fs sz
=x2 Fr −1x2+Fs −1x2+y2 Fr 1y2+Fs 0+z2 Fr 0+Fs 1z2
Maple Solution - Interactive
It is most convenient to define rx,y,z=y−xx y and sx,y,z=z−xx z so that x2 ux+y2 uy+z2 uz becomes x2 Fr rx+Fs sx+y2 Fr ry+Fs sy+z2 Fr rz+Fs sz.
Define r,s, and u
Context Panel: Assign Name
Compute x2 ux+y2 uy+z2 uz and simplify the result to 0
Calculus palette: Partial-derivative operator
Context Panel: Evaluate and Display Inline
Context Panel: Simplify≻Simplify
x2 ∂∂ x u+y2 ∂∂ y u+z2 ∂∂ z u = x2⁢D1⁡F⁡y−xx⁢y,z−xx⁢z⁢−1x⁢y−y−xx2⁢y+D2⁡F⁡y−xx⁢y,z−xx⁢z⁢−1x⁢z−z−xx2⁢z+y2⁢D1⁡F⁡y−xx⁢y,z−xx⁢z⁢1x⁢y−y−xx⁢y2+z2⁢D2⁡F⁡y−xx⁢y,z−xx⁢z⁢1x⁢z−z−xx⁢z2= simplify 0
To work from first principles, obtain and simplify the following derivatives.
Separately obtain and simplify the partial derivatives ux,uy, and uz
∂∂ x u = D1⁡F⁡y−xx⁢y,z−xx⁢z⁢−1x⁢y−y−xx2⁢y+D2⁡F⁡y−xx⁢y,z−xx⁢z⁢−1x⁢z−z−xx2⁢z= simplify −D1⁡F⁡−−y+xx⁢y,−−z+xx⁢z+D2⁡F⁡−−y+xx⁢y,−−z+xx⁢zx2
∂∂ y u = D1⁡F⁡y−xx⁢y,z−xx⁢z⁢1x⁢y−y−xx⁢y2= simplify D1⁡F⁡−−y+xx⁢y,−−z+xx⁢zy2
∂∂ z u = D2⁡F⁡y−xx⁢y,z−xx⁢z⁢1x⁢z−z−xx⁢z2= simplify D2⁡F⁡−−y+xx⁢y,−−z+xx⁢zz2
Obtain and simplify rx,ry,rz,sx,sy, and sz
∂∂ x r = −1x⁢y−y−xx2⁢y= simplify −1x2
∂∂ x s = −1x⁢z−z−xx2⁢z= simplify −1x2
∂∂ y r = 1x⁢y−y−xx⁢y2= simplify 1y2
∂∂ y s = 0
∂∂ z r = 0
∂∂ z s = 1x⁢z−z−xx⁢z2= simplify 1z2
Assemble the terms of the chain rule as per the Mathematical Solution above.
Maple Solution - Coded
Apply the diff and simplify commands to evaluate the expression x2 ux+y2 uy+z2 uz
simplifyx2 diffu,x+y2 diffu,y+z2 diffu,z = 0
Separately obtain and simplify ux,uy, and uz
Apply the diff and simplify commands.
simplifydiffu,x = −D1⁡F⁡−−y+xx⁢y,−−z+xx⁢z+D2⁡F⁡−−y+xx⁢y,−−z+xx⁢zx2
simplifydiffu,y = D1⁡F⁡−−y+xx⁢y,−−z+xx⁢zy2
simplifydiffu,z = D2⁡F⁡−−y+xx⁢y,−−z+xx⁢zz2
Obtain and simplify the derivatives rx,ry,rz and sx,sy,sz
simplifydiffr,x = −1x2
simplifydiffs,x = −1x2
simplifydiffr,y = 1y2
simplifydiffs,y = 0
simplifydiffr,z = 0
simplifydiffs,z = 1z2
<< Previous Example Section 4.3
Next Example >>
© Maplesoft, a division of Waterloo Maple Inc., 2023. All rights reserved. This product is protected by copyright and distributed under licenses restricting its use, copying, distribution, and decompilation.
For more information on Maplesoft products and services, visit www.maplesoft.com
Download Help Document